Legal Consequences of Unregistered Fiduciary Guarantee Deeds on The Agreements Validity - Rismawati, Irma (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to examine the legal protection of creditors in fiduciary guarantee credit agreements. The method used is normative research. The results show that the provision of legal protection for creditors in the case of unregistered fiduciary credit guarantee agreements begins from the signing of the notarized fiduciary guarantee deed and is then confirmed through registration. Registration of fiduciary guarantees must uphold the principle of publicity and ensure legal certainty for creditors in recovering their debts. The details of the law on unregistered fiduciary guarantee deeds against the validity of the guarantee agreement are the invalidity of ownership of the promised goods. This is caused by notarial deeds that are not consistently documented at the fiduciary registration office or only rely on personal deeds, thus harming the executor of the deed and causing creditors to lose priority rights.